Tinjauan Yuridis Perjanjian Jual Beli Mystery Box di E-Commerce - Apriliani; Benny Djaja; Maman Sudirman (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines the legal aspects of mystery box sales transactions in e-commerce, which raise legal challenges, particularly regarding the validity of contract objects and consumer protection. The object of mystery boxes is often unknown to consumers, potentially leading to breach of contract. Under civil law, this may violate Articles 1320 and 1238 of the Civil Code. According to Law No. 8 of 1999 on Consumer Protection, the lack of clarity in mystery box contents may violate the consumer's right to accurate information and cause harm. This study emphasizes the importance of regulation and consumer education to ensure fair and lawful transactions.